2016
DOI: 10.1038/ngeo2633
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Southern Ocean marine productivity due to fertilization by giant icebergs

Abstract: The Southern Ocean is a significant sink in the ocean component of the global carbon cycle, contributing ~ 10% of the ocean's total carbon sequestration through a mixture of chemical and biologically-driven processes 5 . However, its contribution is at a lower level than that of the smaller South Pacific and Indian Oceans 5 , due to its low concentration of dissolved iron, an important trace nutrient for primary production 6 . Atmospheric dust is a major background source of iron to the region 7 , but iron-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(160 citation statements)
references
References 25 publications
3
151
2
Order By: Relevance
“…This result is contradictious to the calculations of Duprat et al (2016). They found an increased phytoplankton concentration within the iron-containing meltwater trail of the giant Antarctica icebergs.…”
Section: Minimizing Ch 4 Emissions From Sediments and Igneous Bedrockcontrasting
confidence: 56%
“…This result is contradictious to the calculations of Duprat et al (2016). They found an increased phytoplankton concentration within the iron-containing meltwater trail of the giant Antarctica icebergs.…”
Section: Minimizing Ch 4 Emissions From Sediments and Igneous Bedrockcontrasting
confidence: 56%
“…Downstream of island plateaus, such as those at Kerguelen (Blain et al, 2001(Blain et al, , 2007, Crozet ice melt (van der Merwe et al, 2011), glacial runoff (Hawkings et al, 2014;van der Merwe et al, 2015) and melting icebergs (Duprat et al, 2016). Primary production downstream of subantarctic island systems is typically dominated by diatoms (Smetacek et al, 2004;Quéguiner, 2013), a microphytoplankton group generally considered to promote carbon export out of the mixed layer directly by sinking (Smetacek, 1985;Newton, 1995, 1999) or indirectly by sustaining faecal pellet-productive food webs (Smetacek et al, 2004;Manno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…33 Hood et al (2009) observed that the high bioavailability of dissolved organic matter (DOM) in 34 glacial streams had a high impact on marine microorganisms in the coastal zone. Additionally, 35 significantly increased chlorophyll levels have been observed around icebergs during the melting 36 of giant icebergs (Duprat et al, 2016), which suggests that the DOM in icebergs can influence 37 microbial activities and can have a further impact on the net primary productivity in the ocean 38 (Wu and Hou, 2017). Due to the high abundances and large degree of chemical diversity of 39 DOM in global glacial streams (e.g., C, N, P, and S) (Fegel et The Tibetan Plateau (TP) is referred to as the "Water Tower of Asia", as it is the source of the 43 ten largest rivers in Asia, which feed more than 1 billion people.…”
mentioning
confidence: 99%